Model Problem Based Learning Berbantuan GeoGebra dan Model Realistic Mathematics Education terhadap Representasi Matematis Siswa ditinjau dari Gaya Kognitif - Amalia, Sofri Rizka; Purwaningsih, Dian; Widodo, An Nur Ami; Fasha, Eka Farida (Jurnal Elemen, 2020)
This study aims to determine the differences in students' mathematical representations through the Problem Based Learning (PBL) model assisted by GeoGebra and Realistic Mathematics Education (RME) models, differences in the mathematical representation of students through GeoGebra-assisted PBL models with the RME model in terms of learning styles Field Independent (FI) and Field Field (FI) Dependent (FD). The research used was Quasi-experimental research. The population is grade XII students, and the sample used is the science class 1, and science 2. The data were collected by tests. Data analyzed using variance and independent t-test. This research results in a difference between students' mathematical representation through the GeoGebra-assisted PBL model and the RME model. The difference in students' mathematical representation through the GeoGebra-assisted PBL model and the model of the RME in terms of the FI learning style. At the same time, for FD, there is no significant difference.